The STUDENTS’ PERCEPTION ON ONLINE LEARNING CLASS DURING COVID 19 PANDEMIC - Sri Erma Purwanti; Maizarah (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of this study was to find out the students’ perception on online learning class during covid 19 pandemic. Sample of this study were 16 students of the third semesterand the fifth semester of English Study Program at Islamic University of Indragiri. The research method used in this study was a descriptiveresearch. Researchers gave questionnaire and interview about student’s perception on online learning class during covid 19 pandemicto collect the data. After the data has been collected, it was found that the data from questionnaire shown that the percentage is 52,97 %, it can be written that the students’ perception on learning online class during covid 19 pandemic wasNeutral, because 52,97% was in range 60%-79,99%. This finding means that the students do not refuse learning online classduring covid 19 pandemic but also do not accept as whole since some obstacles they faced during online class. The poor connection and less of interaction made most of the learners did not have deep understanding of the material as in offline class.